Caffeic acid phenethyl ester (CAPE): cornerstone pharmacological studies and drug delivery systems - Yordan Yordanov (Pensoft Publishers, 2019)
Propolis is a natural product with a plethora of biological effects, utilized by traditional medicine since antiquity. However, its application as a pharmaceutical is hindered by its variable composition and difficult standardization. CAPE has been shown to be a major component of propolis, with a large contribution to its pharmacological effects, among which the anti-inflammatory, antioxidant and antineoplastic have been attracting most attention. The current review article aims to present the cornerstone pharmacological studies of CAPE throughout the years, following its discovery, which confirmed its primary importance among propolis constituents and opened the path to its intensive research as a potential pharmaceutical. We present the diversity of drug delivery systems of CAPE, which have been developed to improve its efficacy in in vitro and in vivo disease models and discuss their primary promises and weaknesses. The increased interest in recent years over more practical approaches of CAPE research such as its pharmaceutical formulation comes to show that it has a potential to become commercialized as a pharmaceutical.